A rare case of cutaneous melioidosis manifesting as infective panniculitis: a case report - Tanat Yongpisarn; Pitak Santanirand; Suwichak Chairanaicharoen; Teerapong Rattananukrom (BMC Infectious Diseases)
Abstract Background Melioidosis, caused by the gram-negative bacterium Burkholderia pseudomallei, is a heterogeneous disease with diverse clinical manifestations, including cutaneous involvement in 10–20% of cases. Case presentation We report the first documented case of infection-induced panniculitis caused by direct inoculation of B. pseudomallei. A 32-year-old woman from Mukdahan, Thailand, with chronic myeloid leukemia treated with a tyrosine kinase inhibitor, was hospitalized for allogenic stem cell transplantation. Three days before admission, she developed a solitary erythematous papule on her left forearm, which rapidly progressed to a tender subcutaneous nodule following chemotherapy. Her hobby of caring for cacti exposed her to soil and caused repeated cactus pricks on her upper extremities. Incisional biopsy of the lesion revealed mixed lobular and septal neutrophilic panniculitis with ischemic fat necrosis, without evidence of vascular occlusion or vasculitis. B. pseudomallei was isolated from a tissue aerobic culture, while blood cultures were negative. She was diagnosed with cutaneous melioidosis. After intensive treatment, the lesion healed, leaving a hyperpigmented patch and a biopsy scar. Conclusion This case highlights the importance of considering melioidosis in patients presenting with panniculitis, particularly those with immunosuppression, minor trauma, and exposure in endemic regions.